(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
In this article I propose to read the Husserlian notion of ‘motivation’ by comparison with the Kantian Schematism, in order to understand its peculiar status and time frame. I maintain that motivations – like a third synthesis in addition to retention (perception) and recollection (reproduction) – mediate and organize the flux of retentions and protentions by intercession of external supports (material, artificial and cultural). Thus, they offer the means to thematize history and, consequently, to recast the transcendental basis of Phenomenology taking the opacity of consciousness into serious account.